ChemInform Abstract: Chemo‐Enzymatic Reaction Sequence for the Synthesis of Dihydroxyacetone Phosphate (DHAP) Stock Material. Issue 21 (2nd May 2013) - Karmee, Sanjib Kumar
Abstract Glycerol is converted to the protected dihydroxy acetone precursor (XI) via a seven‐step chemo‐enzymatic methodology.